KAJIAN TEORITIK PENGARUH GEOMETRI DAN TWIST ANGLE TURBIN HYDROKINETIK SAVONIUS TERHADAP KOEFISIEN DAYA - Kurniawan, Yudi (Sekolah Tinggi Teknologi Adisutjipto, 2017)
The use of fossil energy sources for electric power generation tends to increase while the availability of fossil energy is very limited. New renewable energy sources promise solutions for human dependence on fossil energy sources Dependence on fossil energy will have an impact on the high cost of distributing electricity to remote areas. The picohydro power plant using a very simple savonius hydrokinetic turbine is one of the solutions for remote areas. The purpose of this paper is to obtain the optimum design of the blade hydrokinetic savonius with a relatively easy design method. Based on the results of the study, the geometry and design of savonius hydro quatern turbine are able to produce power coefficient (CP) 13.99 with specification of aspect ratio H / D = 1; end plate Do / D = 1,1; turbine diameter (D) = 82 mm and plate thickness 2 mm, number of blade 3 and twist angle (α) 150.